EFFECTS OF PENTAGAMAVUNONAT-0 SODIUM ON RAT ISOLATED-AORTIC SMOOTH MUSCLE CONTRACTION - Nugroho, Agung Endro; Sendari, Siti; Soraya, Fenthy; Margono, Supardjan A. (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Natrium pentagamavunonat-0 merupakan bentuk garam dari senyawa pentagamavunon (PGV-0). Modifikasi PGV-0 menjadi bentuk garam dimaksudkan untuk meningkatkan kelarutannya. Pada penelitian ini, natrium PGV-0 diuji pengaruhnya terhadap kontraksi otot polos aorta terisolasi yang diinduksi agonis reseptor a1 adrenergik, yaitu fenilefrin. Disamping itu, natrium PGV-0 juga dipelajari efek relaksasi pada organ tersebut. Hasil penelitian menunjukkan bahwa natrium PGV-0 menghambat kontraksi otot polos aorta tikus secara bermakna. Senyawa tersebut dapat menurunkan baik harga pD2 maupun efek maksimum dari fenilefrin. Disampimg itu, natrium PGV-0 menunjukkan efek relaksasi yang poten pada organ tersebut, dengan nilai pD2 sebesar 4,41. Berdasarkan hasil tersebut disimpulkan bahwa natrium PGV-0 menunjukkan efek yang poten pada otot polos aorta terisolasi yang diinduksi agonis reseptor a1 adrenergik.   ABSTRACT PGV-0 is reported possessing some pharmacological effects such as anti-cancer, anti-allergy, anti-inflammatory, anti-oxidative etc. Its effects are more potent than curcumin. However, this compound has limitation in its solubility. Modifying the compound to its salt form is supposed to overcome this problem. The aim of the research is to investigate the effects of PGV-0 sodium on rat isolated-aortic smooth muscle contraction, and its relaxant effect on the tissue. The study was conducted using an isolated organ technique with an isotonic transducer. The percentage of response either contraction or relaxation was then plotted as a logaritmic scale of concentration-response curve to calculate pD2 value, a negative logaritmic of concentration of drug inducing 50% of maximum effect. The results have shown that treatment of PGV-0 sodium obviously inhibited the contraction of rat isolated-aortic smooth muscle induced by phenylephrine. The compound could decrease both pD2 and Emax values of phenylephrine significantly. The results indicate that PGV-0 sodium could attenuate both potency and intrinsic activity of contraction effect of phephylephrine. Besides, the compound also stimulated relaxant effects to a single phenylephrine contraction with pD2 value of 4.41. The compound could restore phenylephrine-induced tension into baseline level. Based on the results, PGV-0 sodium showed potent effects on rat isolated-aortic smooth muscle.